Visualization of bubbles generation of electrical-driven EndoActivator tips during solutions activation in a root canal model and a modified extracted tooth: A pilot study - Harry Huiz Peeters; Elvira Theola Judith; Ketut Suardita; Latief Mooduto (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2022)
Background: EndoActivator, a sonically-driven canal irrigation system (Dentsply Tulsa Dental Specialties, Tulsa, OK), has been developed for activating root canal irrigants, and has recently been released onto the market. Purpose: To obtain an initial understanding of bubbles generation of electrical EndoActivator tips during activation of the irrigant in a transparent root canal model and a modified extracted tooth. Methods: A modified extracted tooth and a straight glass model were filled with a solution containing 17% EDTA or 3% NaOCl. A medium activator tip 22-mm polymer noncutting #25, 0.04 file driven by an electrical sonic hand-piece at 190 Hz (highest level) induced pressure waves that produced macro- and micro-bubbles. The physical mechanisms involved were visualized using a Miro 320S high-speed imaging system (Phantom, Wayne, NJ, USA) with high temporal and spatial resolutions. The imaging system acquired images at 25,000 frames per second with 320×x240 pixels per image, and attached a 60-mm f/2.8 macro lens (Nikon, Tokyo, Japan). Results: The end of the tip did not generate bubbles formation. Disruption of surface tension at the air–solution system in the glass canal model by an electrical sonic driven EndoActivator tip generated bubbles in the solution. However, it did not occur at the system of solution–air interfaces in the glass canal and modified extracted tooth. Conclusion: The physical mechanism of the solution activated by an electrical sonic driven EndoActivator tip in generting bubbles formation is because the surface tension at the air–solution system disruption. No bubbles formation occurred in the solution in the restricted space either in the solution-air system or modified extracted tooth. Better understanding of the physical mechanisms that relate specifically to the activation behaviour of EndoActivator tips in solutions is key to improving the cleaning mechanism that applies during root canal treatment.